2014
DOI: 10.1086/bblv226n1p8
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation and the Reproductive Biology of the Hawaiian Reef-Building Coral Montipora capitata

Abstract: Environmental conditions can influence the physiology of marine organisms and have important implications for their reproductive performance and capacity to supply new recruits. This study examined the seasonal reproductive patterns of the coral Montipora capitata in habitats exposed to different sedimentation regimes. Although M. capitata is a main reef-building coral in the Hawaiian Archipelago, little is known about the gametogenic cycle and reproductive ecology of this important species. Our results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 46 publications
3
45
1
Order By: Relevance
“…While there is debate about the role that solar irradiance plays in driving spawning synchrony (Keith et al, 2016;Van Woesik et al, 2006), it has been shown that insolation correlates to egg maturation (Padilla-Gamiño et al, 2014). In order to simulate this annual variation in photon intensity reaching the coral, 22-year irradiation averages from each study site were converted into data for LED programming.…”
Section: Solar Irradiancementioning
confidence: 99%
“…While there is debate about the role that solar irradiance plays in driving spawning synchrony (Keith et al, 2016;Van Woesik et al, 2006), it has been shown that insolation correlates to egg maturation (Padilla-Gamiño et al, 2014). In order to simulate this annual variation in photon intensity reaching the coral, 22-year irradiation averages from each study site were converted into data for LED programming.…”
Section: Solar Irradiancementioning
confidence: 99%
“…As one of the two most common reef-building corals in Kāneʻohe Bay, M. capitata is found in high density and across a variety of depths and reef habitats 51 , 52 . Furthermore, since M. capitata is highly synchronized in its gametogenesis and spawning behavior 59 , 60 and has more gametes per bundle than Montipora spp . (Table 1 , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In , studies have shown that the coral in Kāneʻohe Bay show some resilience to sediment during gametogenesis and larval survival but not settlement. Padilla-Gamiño et al (2014) looked at the effect of sediment on gametogenesis in M. capitata and found no difference in gamete production between sites with high and low sediment regimes. Perez III et al (2014) exposed larvae of Pocillopora damicornis to substrate covered in varying levels of fine sediment (0.008–0.08 mm).…”
Section: Discussionmentioning
confidence: 99%